Research progress of access control based on blockchain - Zhensheng GAO; Lifeng CAO; Xuehui DU (网络与信息安全学报)
Blockchain technology has the features of decentralization, high credibility, non-tampering and traceability, which can address the trust problem in traditional access control technology.Based on the implementation with blockchain, the unique advantages of applying blockchain to access control are analyzed from two aspects: based on transaction and based on smart contract.Based on the key issues in blockchain application, the current research progress is summarized from three key technologies: dynamic access control, blockchain space optimization, and privacy data protection.Based on the challenges faced by the current blockchain-based access control mechanism, five research prospects are proposed.